1985
DOI: 10.1021/bi00347a041
|View full text |Cite
|
Sign up to set email alerts
|

A nonuniform distribution of excision repair synthesis in nucleosome core DNA

Abstract: We have investigated the distribution in nucleosome core DNA of nucleotides incorporated by excision repair synthesis occurring immediately after UV irradiation in human cells. We show that the differences previously observed for whole nuclei between the DNase I digestion profiles of repaired DNA (following its refolding into a nucleosome structure) and bulk DNA are obtained for isolated nucleosome core particles. Analysis of the differences obtained indicates that they could reflect a significant difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…5 and 6), it is important to understand the influence of this packaging on the distribution of UV photoproducts, especially since the location of these lesions may be a significant factor in determining their removal by repair enzymes (7)(8)(9). Several studies have indicated that, at the level of total genomic DNA, PD form randomly (8)(9)(10), indicating that there is no significant bias between large domains of chromatin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 and 6), it is important to understand the influence of this packaging on the distribution of UV photoproducts, especially since the location of these lesions may be a significant factor in determining their removal by repair enzymes (7)(8)(9). Several studies have indicated that, at the level of total genomic DNA, PD form randomly (8)(9)(10), indicating that there is no significant bias between large domains of chromatin.…”
mentioning
confidence: 99%
“…Using exonuclease III as a probe, it was determined that the 5' and 3' end regions of core DNA are markedly enhanced in repair-incorporated nucleotides. A best-fit analysis of the data indicated that an "50-base central region of core DNA (between positions 62 and 114 from the 5' end) could be devoid of newly synthesized repair patches (7). Since this nonuniform distribution could result from either less efficient repair in the central region of nucleosomes or a nonuniform distribution of UV-induced lesions in core DNA, it was of immediate interest to "map" the location of these lesions within core DNA at the single nucleotide level.…”
mentioning
confidence: 99%
“…Despite this important clinical implication, differential repair in mammalian genomes is not completely understood; in particular, the mechanistic basis of damage-specific and sequence-dependent hierarchies of excision remains obscure. Undoubtedly, DNA repair is influenced by local chromatin compaction (14,15); however, at least in the human p53 gene, no clear correlation between the pattern of DNase I or micrococcal nuclease cleavage and the repair efficiency of UV-induced lesions could be detected (16). In view of these findings, we elaborated on the hypothesis that site-specific changes in DNA conformation may contribute significantly to the observed excision repair variability (17,18).…”
Section: Mammalian Nucleotide Excision Repair (Ner)mentioning
confidence: 98%
“…There is an early rapid phase (lasting 3-6 h after irradiation) and a late slow phase starting between 5 and 16 h after irradiation, depending on the cell strain. It was shown that repair synthesis is randomly distributed in nucleosome core DNA during the late repair phase, whereas there is a distinct bias toward the 5Ј ends of core DNA during the early repair phase (17,18). Surprisingly, during each of these phases, CPDs are repaired at almost equal rates on the inner and outer faces of the DNA helix, relative to the histone surface (18).…”
mentioning
confidence: 99%